Application Of Mini Display For Data Projectionin User Electronics - Veverka, David (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This paper deals with application of a very small display in user specific equipment for projecting data collected at a source machine. The transmission of the data is realized using Bluetooth Low Energy wireless modules. The method of this process is described as well as the complete solution and realization of the prototype.
Keywords: Data collection; Display; Wireless communication; Bluetooth Low Energy